GAMBARAN KONSEP DIRI SISWA DI MTS AL BIDAYAH - Resti Maelani; Heris Hendriana; Devy Sekar Ayu Ningrum (FOKUS (Kajian Bimbingan & Konseling dalam Pendidikan), 2022)
This study aims to determine the description of students who have a negative self-concept at Mts Al Bidayah, West Bandung Regency. The use of methods or methods in this research is descriptive with a qualitative approach. The sampling technique used is purposive sampling technique. The technique in collecting data is using observation and interviews. As for measuring tools, researchers use AUM to reveal various problems students are facing. The result of the research is that there are 2 students who have a negative self-concept. The picture of negative self-concept in these students is as follows: the student has a feeling that other people's views of him are very irregular, the self-concept of the student is too stable and regular or can be said to be too rigid so that this type when he gets new information feels as a threat. and cause anxiety.Keywords:Self concept, Students